Under-utilized germinated horse gram (Macrotyloma uniflorum) protein – Extraction, process optimization, characterization and its use in cookies fortification. (15th April 2022) - Banerjee, Soumitra; Haldar, Swarrna; Reddy, Narendra; Reddy, Roopa; Nagananda, G.S.; Mitra, Jayeeta
Abstract: Proteins were extracted from germinated horse gram (Macrotyloma uniflorum), the under-utilized legume, by alkali treatment and acid precipitation method. Extraction process was numerically optimized by varying parameters like alkali concentration, temperature and alkali to feed ratio. Under optimized parameters, i.e., alkali concentration 0.45% (aqueous NaOH), extraction temperature of 30 °C and alkali to feed ratio of 1:10, it was possible to obtain a yield of 15.29% with protein content being 72.70%. Characterization studies revealed the presence of peptide bonds, amide groups and lack of crystallinity in protein structure. SDS-PAGE revealed the presence of prominent protein bands between 50 and 75 kDa. For preparing cookies, the protein extract was washed with water and dried at 50 °C for over-night. Washed protein extract had 81.83% protein content, which was higher than unwashed protein content, but with lesser yield 13.84%, indicating removal of non-protein content during the washing operation. Sensory evaluation revealed the acceptability of horse gram protein rich cookies, suggesting the potential of using horse gram proteins for food fortification which could help towards prevention of protein malnutrition deficiency. Hence horse gram proteins may be ideal for fortification and assist in providing the necessary nutrition for the unprivileged. Highlights: Optimization of process parameters for horse gram protein extraction It was possible to obtain a yield of 15.29% with protein content being 72.70% Extracted horse gram proteins had similar characteristics to soy protein isolate Commercial potential of extracted protein for fortification in cookie Horse gram protein fortified cookies showed good sensory acceptability